Hardware-Software Co-design for Reconfigurable Field Programmable Gate Arrays Using Mixed-Integer Programming (Informatica, 2025)
Hardware-Software Co-design for Reconfigurable Field Programmable Gate Arrays Using Mixed-Integer Programming